Bioethical implications of research on embryonic stem-cells - Silva Barbosa, Adriana; Lima de Carvalho, Patrícia Anjos; Nery Ferreira, Luciano; Silva de Oliveira Boery, Rita Narriman; da Silva Sena, Edite Lago (Acta Bioethica, 2013)
Embryonic stem-cells are capable of differentiation in diverse cellular types and be used, in the future, for treating degenerative pathologies and deficiencies. This study aimed at analyzing the main bioethical implications of research withembryonic stem cells and was based on a bibliographic revision of articles from the Virtual Health Library and the CAPES Portal de Periódicos. This analysis demonstrated that science is still incapable of establishing when human life begins, that the use of embryos for obtaining cells does not achieve consensus among researchers and that medical treatment based on stem cells are still not a reality. It is important to stress the importance of studies with embryonic stem cells but advances do not mean immediate application that may not correspond to expectations and need social control.